Processo de manufatura por soldagem MIG/MAG TIG híbrida - Campos, Jose Roberto de (2024)
Additive Manufacturing (AM) operates directly with advanced technology and skilled labor to develop high-quality parts with great flexibility. Welding processes are part of this context, contributing to the production of non-serial parts with high added value. The objective of this study is to evaluate the influence of process variables on additive manufacturing by arc deposition using the hybrid MIG/TIG (MADA) process of soft martensitic stainless steel 410NiMo. In this study, it was found that TIG remelting caused a significant change in the delta ferrite precipitation process, which ceased to present an equiaxed grain morphology and began to form a skeletal delta precipitation network. Tensile strength was more influenced by the position of the test specimen extraction, with a reduction in plastic deformation observed in specimens extracted near the end of the deposited wall. When the influence of TIG remelting was analyzed, an increase in mechanical strength and a marginal growth in plastic deformation capacity were observed. The application of the hybrid MIG additive manufacturing technique, followed by TIG remelting, proved to be viable, providing significant improvements in the mechanical properties of the deposits made by MADA.